A Gestão da Informação aplicada ao acervo do Diário de Natal/O Poti: um enfoque na descrição arquivística e na curadoria de conteúdo através de um sistema computacional - Silva, Wellington Rodrigues da (2020)
Currently in the custody of the Federal University of Rio Grande do Norte (UFRN), which is responsible for its preservation and dissemination, the journalistic collection of the Diário de Natal / O Poti represents an extremely rich collection for the production of knowledge on various areas of knowledge , such as economics, politics, arts, public administration and history. Given this context, the general objective of this research was: to analyze the elements of archival description present in national and international standards to simulate their applicability on the collection of Diário de Natal / O Poti in a computer system. The specific objectives were: a) To identify, through documentary research, the national and international standards of archival description currently in force; b) Define the archival functions, the elements of description and metadata to be applied in the organization and technical processing of the collection; c) Format the Collection Arrangement Chart based on the documentary types and collections identified; d) To elaborate content curation processes aiming to contextualize the collection and add value to the information; e) Define the best computer system solution to be used to simulate the practical application of standardization and content curation; and f) Validate the computer system database in order to exemplify the practical application of standardization and its advantages in the dissemination of information and data exchange. Bearing in mind that these interventions fall within the scope of Information Science, authors were researched that deal with Document Management, Archivology and file organization, providing a reflection on how these disciplines relate to informational treatment. The chosen methodology was action research, where knowledge is produced based on the realization of a research directed to a specific theme and, simultaneously, an action is produced aiming at the modification of a given reality. The data collection procedures used were unstructured interviews, participant observation and documentary research, and content analysis was applied to address the inferences and generate the results. The institutional validation of the research with the specialists, those responsible for the collection, was carried out through a focus group. The general objective was achieved with the development of a computational prototype to simulate the national and international standards of archival description currently in force and the content curation processes and, as a result, proposals were presented that allow the treatment of this documentary mass as recommended by the International Council of Archives (CIA). It is hoped that this research will contribute to an efficient classification, description and dissemination of the newspaper Diário de Natal/O Poti, thus creating an environment that allows the creation of knowledge.